PENERAPAN MODEL PROBLEM SOLVING DALAM MENINGKATKAN KEMAMPUAN HOT (HIGHER ORDER THINKING) SISWA SDN BANYU LANDAS - Silvia Uyani (Vidya Karya, 2016)
Abstract: This research relates to the implementation of Problem Solving model in Banyu Landas Elementary School. The research objective is to increase students’ Higher Order Thingking Skills (HOTS). The research was conducted by using classroom action research (CAR) method through 2 cycles. Ten six class students of SDN Banyu Landas were used as research subject. The data collection used obeservation sheets and HOT oriented achievement test. The data were qualitatively analyzed with percentage technique. The result of research stated that (1) students’ Higher Order Thingking Skills (HOTS) increased from analysis skills 77,85% in the first cycle up to  synthesys skills 86,58% in the end of second cycle (2) the quality of teacher’s activity increased  from 58,41% in the first cycle  up to 71,14% in the end of second cycle; (2) students’ activity incresed  from 68,39% in the first cycle  up to 70,10% in the end of second cycle.              Keywords: Higher Order Thinking Skills, teacher activity, student activity , Problem Solving. Abstrak: Penelitian ini berkenaan dengan penerapan model Problem Solving di SDN Banyu Landas. Tujuan penelitian adalah untuk meningkatkan kemampuan berpikir tingkt tinggi (Higher Order Thingking Skill/HOT) siswa. Penelitian ini dilakukan dengan menggunakan rancangan penelitian tindakan kelas dalam 2 siklus. Subyek penelitian adalah 10 orang siswa kelas VI SDN Banyu Landas. Pengumpulan data menggunakan lembar observasi dan tes hasil belajar berorientasi HOT. Data dianalisis secara kualitatif dengan teknik persentase. Hasil penelitian menunjukkan bahwa: (1) kemampuan berpikir tingkat tinggi (Higher Order Thingking Skill/HOT) peserta didik meningkat dari kemampuan analisis 77,85% pada awal siklus I menjadi kemampuan sintesis 86,58% pada akhir siklus II kualitas, (2) aktivitas guru meningkat dari 58,41% pada siklus 1 menjadi menjadi 71,14%  pada siklus 2; (2) aktivitas siswa meningkat dari 68,39% pada siklus 1 menjadi 70,10% pada siklus II. Kata kunci: HOT (Higher Order Thinking) skills, aktivitas guru, aktivitas siswa, Problem Solving